2004
DOI: 10.1123/jtpe.23.1.88
|View full text |Cite
|
Sign up to set email alerts
|

A Developmental Intervention Via the Teaching Portfolio: Employing the Teaching/Learning Framework

Abstract: Nine teacher candidates from each of two PETE programs, University A and University B, developed teaching portfolios over three consecutive semesters of comparable courses. University A teacher candidates underwent a deliberate, developmental portfolio intervention based on the Teaching/Learning Framework (Sprinthall & Thies-Sprinthall 1983), while University B candidates employed a series of portfolio categories based on reflective practice theory (Wallace, 1991) to guide their developmental growth. All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Zhu, 2011). Some of the studies included in this systematic review show that written reflection differentiates the reflective component of teacher practice (e.g., pedagogical content knowledge, content and social issues of teaching), which increases the depth, critical, and thoughtful content of reflection (Senne & Rikard, 2004;Tsangaridou & Polemitou, 2015). These results corroborate several authors (e.g., Kember, McKay, Sinclair, & Wong, 2008;Standal & Moe, 2013;Tsangaridou & Polemitou, 2015), who also argue that written reflections can promote the development of reflection.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Zhu, 2011). Some of the studies included in this systematic review show that written reflection differentiates the reflective component of teacher practice (e.g., pedagogical content knowledge, content and social issues of teaching), which increases the depth, critical, and thoughtful content of reflection (Senne & Rikard, 2004;Tsangaridou & Polemitou, 2015). These results corroborate several authors (e.g., Kember, McKay, Sinclair, & Wong, 2008;Standal & Moe, 2013;Tsangaridou & Polemitou, 2015), who also argue that written reflections can promote the development of reflection.…”
Section: Discussionsupporting
confidence: 84%
“…Within these studies, the majority used written reflections (n=6) (Garrett longitudinal design, with the quantitative methodology being a quasi-experimental design (Senne & Rikard, 2002, 2004. Although one of these studies included a control group, the authors did not acknowledge an experimental design given the number of participants (Senne & Rikard, 2004). The other was cross-sectional with an exploratory design (Keay, 2006).…”
Section: Strategies and Theoretical Framework Applied For The Develop...mentioning
confidence: 99%
See 2 more Smart Citations
“…In this group of studies, a variety of strategies were proposed to prepare teachers to become more reflective. These include: a) a field-based elementary physical education methods course (Sebren, 1995), and; b) teaching portfolio (Senne and Rikard, 2002;Senne and Rikard, 2004). The other two studies (15.4%) reported that professional development program enable PE teachers to hold more positive attitude for teaching (Light and Georgakis, 2005;Xiang, Lowy and McBride, 2002).…”
Section: Pre-service Teachersmentioning
confidence: 99%